The Effectiveness of the Stairs&Cigarettes Game in Anti-Smoking Education for High School Students - Alfiah Lulu fuadiyah; Hendro Yulius Suryo Putro; Qomario Qomario (STKIP Al Islam Tunas Bangsa dan HEPI, 2026)
Smoking among adolescents remains a health problem that requires serious attention, particularly through educational approaches tailored to the characteristics of students. This study aims to analyze the effectiveness of the Stairs & Cigarettes game in anti-smoking education for high school students. The study used a quasi-experimental method with a one-group pretest–posttest design. The subjects were high school students who were given a gamification-based educational game. The research instrument was a questionnaire on understanding the dangers of smoking compiled based on the Health Belief Model construct, including perceived susceptibility, perceived severity, perceived benefits, perceived barriers, cues to action, and self-efficacy. Data were analyzed using inferential statistics to determine differences in scores before and after treatment. The results showed a significant increase in students' understanding after participating in the Stairs & Cigarettes game. This increase reflects positive changes in the perception of smoking risks, the benefits of anti-smoking behavior, and the strengthening of self-efficacy in refusing smoking invitations. These findings indicate that the Stairs & Cigarettes game not only improves cognitive aspects but also strengthens students' psychosocial readiness.